IZUM v vlogi UNESCOVEGA regionalnega centra - Šoštarič, Davor (Organizacija znanja, 2016)
At its 36th General Assembly in November 2011, UNESCO adopted the decision to grant IZUM the status of a category 2 centre. One year later, the Agreement between the United Nations Educational, Scientific and Cultural Organization (UNESCO) and the Republic of Slovenia was signed in Paris, specifying and defining IZUM's functions as a regional category 2 centre under the auspices of UNESCO. The most significant events and our reflections after three years of performing this function are presented.
Keywords: category 2 centre; center II. kategorije; COBISS; COBISS.Net; current research information system; E-CRIS; informacijski sistem o raziskovalni dejavnosti; IZUM; Jugovzhodna Evropa; knjižnični informacijski sistem; library information system; South-Eastern Europe; UNESCO